How does women’s life satisfaction respond to retirement? A two-stage analysis - Zhu, Rong (My University, 2015)
We quantify the adjustment of women’s life satisfaction to retirement as a two-stage process. The transition to retirement leads to an immediate increase in women’s life satisfaction. After becoming retired, their life satisfaction declines with the duration of retirement.
Keywords: Satisfaction; Benefits and Payments; Ageing -- Retirement; Ageing; Satisfaction; Benefits and Payments; Ageing; Retirement; Ageing